Proccedings of 10th International Conference "Environmental Engineering" 2017
DOI: 10.3846/enviro.2017.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carbon Dioxide in Kindergartens in Poland

Abstract: Abstract. Children in kindergartens spend between five and ten hours a day, the quality of air inside is very important. Kindergartens are public buildings. Kindergartens in Poland do not have mechanical ventilation, most often use stack ventilation, which is frequently aided by airing. The three considered buildings were located in eastern Europe. The main objective of the research was to evaluate the interior conditions, especially with regard to carbon dioxide concentration. In the afternoon, the permissibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The dimensions of the rooms were measured with a Bosch DLE 70. Instrument parameters are given in publications [7,17]. Figure 2 presents the results of measurements of carbon dioxide concentration (one series of the measurements).…”
Section: Methodsmentioning
confidence: 99%
“…The dimensions of the rooms were measured with a Bosch DLE 70. Instrument parameters are given in publications [7,17]. Figure 2 presents the results of measurements of carbon dioxide concentration (one series of the measurements).…”
Section: Methodsmentioning
confidence: 99%
“…High CO₂ concentrations and insufficient ventilation were documented in kindergarten classrooms worldwide, according to research conducted in Portugal [22], [23], Poland [24], France [25], Korea [26] and Malaysia [14]. A study in Portugal found that CO2 concentration in kindergarten classrooms was high and several times exceeding the Portuguese standards.…”
Section: Indoor Air Quality Research In the Classroommentioning
confidence: 99%
“…Various types of rooms were analyzed. Among others the residential buildings [4,8], the classrooms [9][10][11], office buildings [6] and preschools [7,12] were examined. The tests of air parameters were also conducted in car cabins [13,14], where is mechanical ventilation and pollution, which is caused by the presence of people, just like in didactic rooms.…”
Section: Introductionmentioning
confidence: 99%